Hsp90 inhibitors in breast cancer: A systematic review - Zagouri, F.; Sergentanis, T.N.; Chrysikos, D.; Papadimitriou, C.A.; Dimopoulos, M.-A.; Psaltopoulou, T. (Breast, 2013)
Purpose: Pharmacological inhibition of Hsp90 shows great promise in breast cancer treatment. This is the first systematic review to synthesize all available data and to evaluate the efficacy and safety of Hsp90 inhibitors in breast cancer. Methods: This study was performed in accordance with the PRISMA guidelines. Eligible articles were identified by a search of MEDLINE and ClinicalTrials.gov databases, using a predefined combination of the terms "breast", "cancer", "Hsp90", "inhibitors". Results: Overall, 19 articles (190 patients) were eligible. The greatest clinical activity has been observed on the field of HER2-positive metastatic breast cancer. However, accumulating data suggest that Hsp90 inhibitors may play a significant role in the treatment of triple negative and aromatase inhibitor-resistant breast cancer. Conclusion: In the last decade, the development of Hsp90 inhibitors has moved forward rapidly; however, no phase III trials have been conducted and none agent has been approved for use in the clinical practice. © 2013 Elsevier Ltd.
Keywords: Alvespimycin; breast cancer; Hsp90 inhibitors; Retaspimycin; Tanespimycin